2013
DOI: 10.1038/pcan.2013.43
|View full text |Cite
|
Sign up to set email alerts
|

Performance of multiparametric MRI in men at risk of prostate cancer before the first biopsy: a paired validating cohort study using template prostate mapping biopsies as the reference standard

Abstract: Background Multi-parametric MRI (mp-MRI) has the potential to serve as a non-invasive triage test for men at risk of prostate cancer. Our objective was to determine the performance characteristics of multi-parametric MRI (mpMRI) in men at risk prior to first biopsy using 5mm template prostate mapping (TPM) as the reference standard. Methods One hundred and twenty nine consecutive men with clinical suspicion of prostate cancer that had no prior biopsy, underwent mpMRI (T1/T2-weighted, diffusion-weighting, dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
83
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 34 publications
(34 reference statements)
9
83
1
2
Order By: Relevance
“…Conversely, 3T MP-MRI with endorectal coil for the identification of suspicious prostate lesions and subsequent MRI/TRUS fusion-guided prostate biopsy has exhibited high levels of sensitivity and negative predictive values (>90%) in detecting clinically significant disease. 8,18 In the current study, we observed an overall CDR of 64.6% which is comparable to the 54% to 63% range reported in the literature. 11,19,20 We observed an AUC of 0.769 (95% CI, 0.703-0.834) for lesion suspicion level on MP-MRI in predicting high-grade CaP, which is 10 percentage points better than the PCPTHG AUC of 0.676 (95% CI, 0.592-0.751; P 5 .091).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Conversely, 3T MP-MRI with endorectal coil for the identification of suspicious prostate lesions and subsequent MRI/TRUS fusion-guided prostate biopsy has exhibited high levels of sensitivity and negative predictive values (>90%) in detecting clinically significant disease. 8,18 In the current study, we observed an overall CDR of 64.6% which is comparable to the 54% to 63% range reported in the literature. 11,19,20 We observed an AUC of 0.769 (95% CI, 0.703-0.834) for lesion suspicion level on MP-MRI in predicting high-grade CaP, which is 10 percentage points better than the PCPTHG AUC of 0.676 (95% CI, 0.592-0.751; P 5 .091).…”
Section: Discussionsupporting
confidence: 87%
“…7 Conversely, it has been demonstrated that magnetic resonance (MR) imaging (MRI) with subsequent MRI/ transrectal ultrasound (MRI/TRUS) fusion-guided biopsy of the prostate has a high level of sensitivity and a high positive predictive value for identifying CaP with a correlation to clinical significance. [8][9][10] In the current study, for the first time to our knowledge, we compared the performance of the PCPTHG and multiparametric-MRI (MP-MRI) in identifying men at risk of high-grade or clinically significant CaP for prostate biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 8663 original studies in English were identified and 15 were analyzed. [2][3][4][6][7][8][23][24][25][26][27][28][29][30][31] The overall quality varied from low to moderate. Fourteen conference abstracts will require followup in future updated versions.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…• Eight eligible studies 2,3,6,7,[23][24][25][26] addressed the first objective. The quality of evidence ranged from poor to moderate.…”
Section: Key Evidencementioning
confidence: 99%
“…Their early experience which enrolled patients up to five years preceding the commencement of PROMIS reported a sensitivity and NPV of 90% and 70% for cancer of any grade [12]. For different definitions of clinically significant disease the ranges of sensitivity and NPV were 94% to 100% and 89% to 100%.…”
Section: Level 1 Evidencementioning
confidence: 99%